Changing outlook for colorectal liver metastasis resection in the elderly. Issue 4 (April 2019) - Tufo, Andrea; Dunne, Declan FJ.; Manu, Nichola; Lacasia, Carmen; Jones, Louise; de Liguori Carino, Nicola; Malik, Hassan Z.; Poston, Graeme J.; Fenwick, Stephen W.
Abstract: Background: This study sought to evaluate the impact of the advancements in clinical care, obtained over the last 20 years, for patients aged 70 and older undergoing liver resection for colorectal liver metastases (CRLM). Methods: Consecutive patients age 70 or older who underwent liver resection for CRLM at Aintree University Hospital (Liverpool, UK) between May 2008 and May 2015 were compared to a dataset of consecutive patients, meeting the same criteria, between 1990 and 2007. An enhanced recovery programme after surgery (ERAS) combined with cardiopulmonary exercise testing (CPET) was introduced in January 2008. Results: The proportion of patients over 70 years undergoing liver resection for CRLM increased over the study period (6% in 1990, 16.3% in 2000, 26.5% in 2005 and 25.8% in 2007). The patients in the later group were more often treated with neoadjuvant chemotherapy (58 vs 34, p = 0.006) and underwent parenchymal sparing surgery, resulting in fewer major hepatectomies (51 vs 111, p < 0.001) and less perioperative morbidity (49 vs 70, p = 0.043) and mortality (3 vs 9, p = 0.229). Although there was shorter disease free survival (DFS) in the later group (DFS at 1, 3 and 5 years was 52.1%, 31.6%, 29% vs. 71.8%, 49.1%, 44.0%)(p < 0.01), similar overall survival (OS) was achieved (OS at 1, 3 and 5 years was 85.4%, 51.6%, 32.8% vs. 81.7%, 42.1%, 27.3%)(p = 0.21). Conclusions: This study demonstrates that, with modern management (ERAS, CPET, neoadjuvant chemotherapy and parenchymal sparing surgery), a greater number of patients with CRLM, over the age of seventy, can undergo liver resection, with improved perioperative outcomes.